The Influence of Work Climate on Nurse Performance: A Scoping Review - Aulia Haerda Diantika; Septo Pawelas Arso; Luky Dwiantoro (GLOBAL HEALTH SCIENCE GROUP, 2024)
Health is a very vital aspect of human life, and the role of nurses is very central in providing quality health services. Nurses must not only have high levels of clinical competency but must also operate in a supportive, positive, and inclusive work environment. However, understanding of the impact of work climate on nurse performance is still limited, especially in hospital environments and health care facilities. This study aims to explore the influence of work climate on nurse performance in the context of health services. The scoping review method was used to identify and summarize relevant literature. We searched for articles from the Google Scholar database and the Garuda Portal from January 2018 to September 2023 using the keywords ‘work climate’ OR ‘performance’ AND ‘nurse performance.’ Inclusion and exclusion criteria were applied to select appropriate articles, and finally, we analyzed the findings of seven articles that met these criteria. The research results show that work climate has a significant impact on nurse performance in various hospital contexts. This finding is strengthened by previous studies that confirm that a positive work environment can increase nurses' motivation and performance.